Teachers’ test construction competencies in examination-oriented educational system: Exploring teachers’ multiple-choice test construction competence - Kissi, Prosper; Baidoo-Anu, David; Anane, Eric; Annan-Brew, Ruth Keziah (Frontiers in Education, 2023)
This study is part of a larger thesis that explored the relationship between multiple-choice test construction competence and the quality of multiple-choice tests among senior high school teachers in Ghana. In all, 157 teachers were selected from four senior high schools in the Kwahu-South District. Three-factor structure emanated from the exploratory factor analysis on teachers’ multiple-choice test construction competence ⎼content validity, item ‘options’ handling, and test items assembling. Teachers in this study perceived more competence in ensuring content validity, followed by test item assembling and handling of ‘options’ (that is, alternatives) of the test items. The study also found serious problems with copies of multiple-choice items teachers have constructed for the students. Findings from this study provide unique and compelling evidence in the Ghanaian context regarding teachers’ perceived test construction competence and analysis of their multiple-choice tests. Implications for policy and practice have been discussed.